(untitled) (Journal of the College of Basic Education, 2022)
Amid the rapid spread of COVID-19 pandemic, universities and schools resorted to e-learning or learning from distance via internet platforms using smart phones and computers. In other words, students sit at their homes waiting for their teachers and lecturers to send them their lessons and lectures via internet and through online learning platforms such as Google Classroom, Schoology, Edmodo, FCC, Zoom, etc. In such a learning method, students become passive (teachers control the flow of the lectures and students only receive the information). Therefore, Students need to be motivated. This article sheds light on the recent trends of motivating students to learn.